The order : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2020)
Gabriel Allon has slipped quietly into Venice for a much-needed holiday with his wife and two young children. But when Pope Paul VII dies suddenly, Gabriel is summoned to Rome by the Holy Father<U+2019>s loyal private secretary, Archbishop Luigi Donati. A billion Catholic faithful have been told that the pope died of a heart attack. Donati, however, has two good reasons to suspect his master was murdered. The Swiss Guard who was standing watch outside the papal apartments the night of the pope<U+2019>s death is missing. So, too, is the letter the Holy Father was writing during the final hours of his life. A letter that was addressed to Gabriel. While researching in the Vatican Secret Archives, I came upon a most remarkable book <U+2026> The book is a long-suppressed gospel that calls into question the accuracy of the New Testament<U+2019>s depiction of one of the most portentous events in human history. For that reason alone, the Order of St. Helena will stop at nothing to keep it out of Gabriel<U+2019>s hands. A shadowy Catholic society with ties to the European far right, the Order is plotting to seize control of the papacy. And it is only the beginning. As the cardinals gather in Rome for the start of the conclave, Gabriel sets out on a desperate search for proof of the Order<U+2019>s conspiracy, and for a long-lost gospel with the power to put an end to two thousand years of murderous hatred. His quest will take him from the Ponte Vecchio in Florence, to a monastery in Assisi, to the hidden depths of the Secret Archives, and finally to the Sistine Chapel, where he will witness an event no outsider has ever before seen<U+2014>the sacred passing of the Keys of St. Peter to a newly elected pope.